[BP.12.07] CARDIAC OUTPUT, CAROTID-FEMORAL PULSE WAVE VELOCITY, AND COGNITIVE FUNCTION IMPAIRMENT IN AN ELDERLY POPULATION. (September 2017) - Chen, C.; Chuang, S.Y.; Cheng, H.M.; Pan, W.H.
Abstract : Objective: Low cardiac output has been associated with impaired cognitive function in heart failure patients. We aimed to investigate the relationship between cardiac output and cognitive function in the elderly general population. Design and method: The Cardiovascular Disease Risk Factors two-Township study (CVDFACTS) was a longitudinal cohort study. The on-going sixth wave survey was started in 2015. A total of 331 seniors aged more than 60 years participated in the sixth wave survey and received the Mini-Mental State Examination (MMSE) to evaluate the global cognitive function. Cardiac and arterial function were assessed by measuring cardiac index (CI), ejection fraction, and end-systolic elastance, carotid-femoral pulse wave velocity (cf-PWV), augmentation index (AI) and arterial elastance. The general linear regression and logistic regression were used to evaluate the associations between MMSE and cardiac output and cf-PWV, respectively. Results: Of all cardiovascular parameters, after adjusting for age, gender, and education, only CI (r = 0.16, p-value = 0.0043) and cf-PWV (r = −0.15, p-value = 0.0082) were positively and negatively associated with MMSE, respectively. CI (median: 2.00 L/min/m 2 ) and cf-PWV (median: 13.69 m/sec) were further classified by median into low and high groups. In the multivariable model adjusting for age, sex, education, body mass index, systolic blood pressure, dyslipidemia and diabetes, compared to those elderly with low cf-PWV and high CI (reference group, n = 84), the adjusted difference of MMSE was −0.83 (p-value = 0.033) for low cf-PWV plus low CI (n = 81), was −0.64 (p-value = 0.101) for those with high cf-PWV plus high CI (n = 83), and −0.09 (p-value = 0.021) for high cf-PWV and low CI (n = 83). Moreover, compared to the reference group, the odds ratio (OR) of impaired cognitive function (MMSE score <26) in the above multivariable model was 4.59 (95% confidence interval: 1.12–18.8) for high cf-PWV and low CI, 4.32 (1.11–16.8) for high cf-PWV plus high CI, and 5.97 (1.34–26.7) for low cf-PWV plus low CI. Conclusions: In an elderly population, lower cardiac output was associated with lower MMSE and a higher risk of impaired cognitive function, independent of cf-PWV, a recognized risk factor for dementia in the elderly.